Oral cancer awareness and its determinants among a selected Malaysian population - Ghani, W.M.N.; Doss, J.G.; Jamaluddin, M.; Kamaruzaman, D.; Zain, R.B. (2013)
Objective: To assess oral cancer awareness, its associated factors and related sources of information among a selected group of Malaysians. Methods: A cross-sectional survey was conducted on all Malaysian ethnic groups aged >= 15 years old at eight strategically chosen shopping malls within a two week time period. Data were analysed using chi-square tests and multiple logistic regression. Significance level was set at alpha<0.05. Results: Most (84.2%) respondents had heard of oral cancer. Smoking was the most (92.4%) recognized high risk habit. Similar levels of awareness were seen for unhealed ulcers (57.3%) and red/white patches (58.0%) as signs of oral cancer. Age, gender, ethnicity, marital status, education, occupation and income were significantly associated with oral cancer awareness (p<0.05). Conclusions: There was a general lack of awareness regarding the risk habits, early signs and symptoms, and the benefits of detecting this disease at an early stage. Mass media and health campaigns were the main sources of information about oral cancer. In our Malaysian population, gender and age were significantly associated with the awareness of early signs and symptoms and prevention of oral cancer, respectively.